Education in Modern China. - Price, R. F. (Taylor and Francis, 2014)
First published in 1970 this re-issues the revised edition of 1979. This book examines the part played both by tradition and by the Cultural Revolution in the educational system of twentieth century China and explores the apparent reversal of policy which took place since the death of Mao. The book discusses the writings of Mao on the nature of man, society and knowledge and his ideas on education. These are then seen in the context of history, philosophy and religion. Educational aims and policies are discussed, showing how factors such as language, geography, economics and the socia.